Environment is crucial to the cooking time of beans - Bruna ARRUDA (Ciência e Tecnologia de Alimentos, 2012)
The objectives of this study were to understand how genotype, storage time, and storage conditions affect cooking time of beans and to indicate storage techniques that do not affect the cooking time. The grains were subjected to five different storage periods and six different storage conditions. The cooking time was estimated using the Mattson Cooker. The data were subjected to analysis of variance and a subsequent adjustment of simple linear regression for deployment of the interactions between the factors. Contrasts were used to determine the best levels of the factor storage condition. Genotype did not impact cooking time when the storage time and storage conditions were considered. Time and storage conditions affect the cooking time of beans in a dependent manner, but time of storage had the biggest influence. The best conditions for long-term storage of beans ensuring a smaller increase in cooking time is plastic storage at low temperatures. Thus, plastic freezer storage is a practical alternative for consumers.